Insights into Zn anode surface chemistry for dendrite-free Zn ion batteries. Issue 20 (6th May 2022) - Hu, Qiang; Hu, Jisong; Li, Yuanxia; Zhou, Xinyi; Ding, Shixiang; Zheng, Qiaoji; Lin, Dunmin; Zhao, Jingxin; Xu, Bingang
Abstract : The zinc-ophobic tetramethylammonium sulfate electrolyte additive and zinc-ophilic ZnO@Cu artificial layer are used to inhibit Zn corrosion and dendrite growth. Abstract : Zn metal at a low cost, high theoretical capacity, and no harm to the environment is considered as the most promising anode for aqueous batteries. However, in the slightly acidic electrolytes, hydrogen evolution and spontaneous Zn corrosion damage the service life of Zn-based batteries and further seriously restrict their large-scale application in energy storage fields. Herein, we first study the corrosion mechanism of Zn in ZnSO4 solution with tetramethylammonium sulfate (TS) additive and report a method for the co-modification of the Zn anode with ZnO@Cu solid solution interface and TS additive. The obtained ZnO@Cu artificial layer and TS additive can not only inhibit Zn corrosion and induce Zn electroplating/peeling on the Zn surface, but also promote uniform deposition of Zn in the battery charge/discharge process. Density functional theory (DFT) calculations and in situ optical microscopy observations reveal the strong zincophilic properties of the ZnO@Cu artificial layer and the distinctive zincophobic mechanism of TS. As a result, this dendrite-free Zn electrode displays low polarization (22.3 mV at 0.25 mA cm −2 ) and high cycling stability (over 4500 h at 0.25 mA cm −2 ), which was also confirmed in an NH4 V3 O8 |ZnO@Cu/Zn-TS full-cell with a capacity retention of 84% after 1500 cycles.